Semarang Zoo Marketing Communication Strategy through Instagram Social Media @SemarangZoo - Fatah, Adi Nur; Santosa, Hedi Pudjo (Budapest International Research and Critics University, 2022)
Instagram is a social media that displays visual content. Instagram can be used to attract public attention by displaying various types of information. Semarang Zoo uses Instagram in maximizing marketing communication strategies. The purpose of this study is to explain the marketing communication message strategy of Semarang Zoo which is carried out through Instagram @SemarangZoo. This study uses a descriptive qualitative approach. The data collection technique was carried out by means of observation, documentation and literature study, where the researcher took screenshots of several uploads on the @SemarangZoo XXgy of compiling messages and focuses on social media. The results of the study explain how the Semarang Zoo displays the content of communication information and creative forms of messages through Instagram @SemarangZoo with a period of April to September 2021.